THE DEVELOPMENT PROGRAM OF ENHANCE TEACHER COMPETENCY ON ENGLISH COMMUNICATION LEARNING MANAGEMENT FOR THE SCHOOL OF WELFARE EDUCATION IN THE NORTHEAST OF THE OFFICE OF SPECIAL EDUCATION BUREAU - Saitumlueng, Em-amorn; Julsuwan, Suwat (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The research article was 1) to study the current condition, the desirable condition, and needs and development a competency enhancement program in communicative English learning management for teachers in the schools of welfare education in the northeast of the Office of Special Bureau. The research was conducted into 2 phases, with the first phase being the study of current condition and desirable condition of enhancing competency in communicative English learning management for teachers in the schools of welfare education in the northeast of the Office of Special Bureau. The sample was 86 school administrators and English teachers from 10 schools of welfare education in the northeast of the Office of Special Bureau through cluster random sampling. The research instrument was questionnaires which include 20 items in a 5-point rating scale format. The statistics used for data analysis were percentage, mean, standard deviation and priority needs index. Phase 2 is the design and evaluation of a competency enhancement program in communicative English learning management for teachers in the schools of welfare education in the northeast of the Office of Special Bureau. The program was created with the best practice approach from 3 master schools through interviews with 6 administrators and teachers. The program was evaluated by 5 experts selected with purposive sampling. The research instrument was an interview form was a semi-structured interview with 4 items and suitability and feasibility assessment form which include 5 items in a 5-point rating scale format. The statistics used to analyze the data were mean and standard deviation. The result of the research revealed that: 1. The current condition of a competency enhancement program in communicative English learning management for teachers is overall at a high level. The desirable condition of a competency enhancement program in communicative English learning management for teachers is overall at the highest level. In terms of needs (PNImodified) in developing a competency enhancement program in communicative English learning management for teachers, the priority needs in descending order are the measurement and evaluation aspect, the instructional media aspect, the instructional activities and the curriculum aspect. 2. The competency enhancement program in communicative English learning management for teachers in the schools of welfare education in the northeast of the Office of Special Bureau consists of 5 parts: 1) principles, 2) objectives, 3) content, 4) development methods, and 5) evaluation. The content is composed of 4 modules: Module 1-curricula, Module 2-instructional activities, Module 3-instructional media; and Module 4-measurement and evaluation. Overall, the program evaluation results are at the highest level of suitability and feasibility.